PENERAPAN STRATEGI PEMECAHAN MASALAH WANKAT-OREOVOCZ DALAM PENINGKATAN LITERASI MATEMATIS SISWA SMP DITINJAU DARI PENGETAHUAN AWAL MATEMATIS (PAM) SISWA - Nego Linuhung (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2015)
The aim of this research to analyze the essence of learning the strategy of Wankat-Oreovocz problem solving as alternative the problem solution. The research design which is used is a non-equivalent control group design by using technique of Purposive Sampling. The Research Subject is all eight grade students of Sukahaji Junior High School with the research sample is VIIIG grade students. The research instrument used in the form is prior mathematical knowledge test (PAM), mathematical literacy test of level 5. Result of the research indicates that: 1) There is the difference of mathematical literacy improvement of level 5 at student who is getting The Strategy of Wankat-Oreovocz Problem Solving (WO) evaluated from the PAM student category (high and low)